Where's Tumpty? - Dunbar, Polly (Somerville, Mass. : Candlewick Press, 2009)
Tumpty the elephant hides by closing his eyes, placing a cardboard box over his head, and lying upside down behind a potted plant, but his friends, including Tilly, can still see him.
"A Tilly and friends book"--Cover.
Booklist.
School Library Journal.
1.5
K-3
Keywords: Animals -- Juvenile fiction; Elephants -- Juvenile fiction; Friendship -- Juvenile fiction; Animals -- Fiction; Elephants -- Fiction; Friendship -- Fiction; Animals -- Fiction; Elephants -- Fiction; Friendship -- Fiction